The Role of Constitutional Reform Act 2005 in Reinforcing the Divisions of Power in the UK - Kime, Redouani, Laid Yacine (جامعة الوادي University of Eloued, 2019)
تهدف هذه الدراسة إلى استكشاف الجوانب المختلفة للتعديل الدستوري لعام 2005 بالإضافة إلى مساهمته في تعزيز فصل السلطات في المملكة المتحدة. المسعى الرئيسي لهذا البحث يدور حول أهمية هذا التعديل في تمهيد الطريق نحو تشكيل منظومة قوية لفصل السلطات. من أجل التحقق من صحة فرضيتنا ، تعتمد الدراسة المنهج الوصفي لتعزيز رؤية البحث. النتائج المتحصل عليها من الدراسة تؤكد بقوة الفرضية المذكورة في دراستنا : أن التعديل الدستوري لعام 2005 ذو أهمية كبيرة من خلال مساهمته في تشكيل نظام حقيقي لفصل السلطات . تنقسم هذه الدراسة إلى فصلين. الفصل الأول يعمل على تقديم نظرة عامة حول التقسيم السياسي للسلطات في المملكة المتحدة قبل إدخال التعديلات الدستورية . الفصل الثاني يدرس جميع الجوانب الرئيسية للتعديل ، كما يلقي الضوء على مساهمته في تعزيز فصل السلطات في المملكة المتحدة. The aim of this study is to explore the various aspects of Constitutional Reform Act 2005 as well as its contribution in strengthening the power’s divisions in the UK. The main question that is investigated in this research is the importance of the reform act in paving the way for more strict doctrine of separation of powers. In order to verify the validity of our hypothesis, the study adopts the descriptive method in order to strengthen the research ‘vision. The results obtained from the study strongly confirm the hypothesis mentioned in our study: Constitutional Reform Act 2005 is of significant importance towards achieving true doctrine of power’s divisions. This study is divided into two chapters. The first chapter works on presenting an overview about the political division of powers in the UK prior to the introduction of the reform changes. The Second one works on introducing the main sections and areas of the Reform Act, it also sheds light on the contribution of the Reform Act 2005 in reinforcing the powers’ doctrine in the UK.
Keywords: الدستور, فصل, السلطات, المملكة المتحدة, مساهمة, تعديل; constitution, contribution, divisions, power , reform, UK